Apportionment of liability in the electronic commerce in Arab countries: a literature review - Hasan, Yahya Y. F.; Zulhuda, Sonny (2012)
The increasing popularity of electronic commerce has shown its problematic side, namely the issue of apportionment of liability. Due to the involvement of several intermediaries, it is often uncertain if those intermediaries would assume responsibility, or to what extent if any, should the transaction goes wrong. The current paper, a research in progress, identifies this issue in the context of e-commerce practices in Arab countries with particular attention to the Palestine. It goes further with a literature review on the peculiar issues related to the e-commerce and the apportionment of liability, and ultimately sheds the light on the direction of research needed in future on the areas of e-commerce law both in the Palestine and the Arab countries generally.